Polymer studies using atomic force microscopy (AFM). Part II. Investigation of chemical reactions and physical processes in polymers - Kaczmarek, H.; Czajka, R.; Nowicki, M.; Wiśniewski, M. (Polimery, 2022)
A review covering 87 references present possibility of monitoring of polymerization (electropolymerization) and polymer grafting processes leading to different morphology of polymers (monolayers, grains). The degradation and modification of polymer surfaces induced by electromagnetic radiation were also observed with AFM (for example, changes of roughness, formation of rows, hills and holes). Examples of AFM studies of following physical phenomena and properties: mechanical roperties, adhesion, friction, elasticity, hardness, hydrophilicity, crystallinity have been presented for broad range of materials. Moreover, use of AFM in other fields (biology, physics) and new, related methods developed on AFM base have been also referred. Broad application of AFM in material sciences may be expected in the future.